2013
DOI: 10.1007/s00403-013-1316-y
|View full text |Cite
|
Sign up to set email alerts
|

Topical herbal medicine combined with pharmacotherapy for psoriasis: a systematic review and meta-analysis

Abstract: This systematic review examines the current state of the evidence for the efficacy and safety of herbal medicines (HMs) used topically in conjunction with anti-psoriatic pharmacotherapy (APP) in the treatment of psoriasis. Searches were conducted in September 2012 of PubMed, EMBASE, Cochrane Library, two Chinese databases (China National Knowledge Infrastructure and Chinese Scientific Journals Full Text Database) and of article reference lists. We included randomized controlled trials published in English, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 33 publications
0
30
0
1
Order By: Relevance
“…& Charlie C. L. Xue charlie.xue@rmit.edu.au these issues but there remains a need for new therapeutic agents and approaches [18,30]. In reviews and meta-analyses of the clinical trial evidence for traditional medicines (TMs) in psoriasis, we identified multiple TMs that show promise of efficacy [21][22][23][24]55]. However, it was possible that outcome data were influenced by bias in trial design and measurement.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…& Charlie C. L. Xue charlie.xue@rmit.edu.au these issues but there remains a need for new therapeutic agents and approaches [18,30]. In reviews and meta-analyses of the clinical trial evidence for traditional medicines (TMs) in psoriasis, we identified multiple TMs that show promise of efficacy [21][22][23][24]55]. However, it was possible that outcome data were influenced by bias in trial design and measurement.…”
Section: Introductionmentioning
confidence: 92%
“…Radix Rehmannia (Di huang) and Radix Salvia (Dan shen) were frequently used in oral preparations. Camptotheca acuminata (Xi shu) and Indigo naturalis (Qing dai) were used topically in the clinical trials but they can also appear in oral preparations [21,22,24]. These four TMs (hereafter called Rehmannia, Salvia, Indigo and Camptotheca) are not typically used in combination or interchangeably, are traditionally regarded as having different functions, and are known to contain different compounds [84].…”
Section: Selection Of Candidates For Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Entre las patologías tratadas con cAM que han sido objeto de estudio se encuentran: cáncer de próstata, de tiroides, de mama, enfermedades dermatológicas y enfermedades ginecológicas, entre otras (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Uso De Las Cam En La Medicina Occidentalunclassified
“…CHM has been extensively used for centuries as a treatment for different diseases and conditions (104). However, the use of Chinese medicine raised serious concerns regarding safety due to unknown composition and amount of plants used (94).…”
Section: Chinese Herbal Remediesmentioning
confidence: 99%